Almost 50 Years of Monomeric Extracellular Ubiquitin (eUb) - Ivette Mendoza-Salazar; Ana Fragozo; Aneth P. González-Martínez; Ismael Trejo-Martínez; Rodrigo Arreola; Lenin Pavón; Juan C. Almagro; Luis Vallejo-Castillo; Francisco A. Aguilar-Alonso; Sonia M. Pérez-Tapia (MDPI AG, 2024)
Monomeric ubiquitin (Ub) is a 76-amino-acid highly conserved protein found in eukaryotes. The biological activity of Ub first described in the 1970s was extracellular, but it quickly gained relevance due to its intracellular role, i.e., post-translational modification of intracellular proteins (ubiquitination) that regulate numerous eukaryotic cellular processes. In the following years, the extracellular role of Ub was relegated to the background, until a correlation between higher survival rate and increased serum Ub concentrations in patients with sepsis and burns was observed. Although the mechanism of action (MoA) of extracellular ubiquitin (eUb) is not yet well understood, further studies have shown that it may ameliorate the inflammatory response in tissue injury and multiple sclerosis diseases. These observations, compounded with the high stability and low immunogenicity of eUb due to its high conservation in eukaryotes, have made this small protein a relevant candidate for biotherapeutic development. Here, we review the in vitro and in vivo effects of eUb on immunologic, cardiovascular, and nervous systems, and discuss the potential MoAs of eUb as an anti-inflammatory, antimicrobial, and cardio- and brain-protective agent.